Tradisi Pengulangan Khutbah Jum’at di Aceh: Dialektika Kehati-Hatian (Ihtiyat) dan Otoritas Dayah: The Tradition of Repeating Friday Sermons in Aceh: The Dialectic of Caution (Iḥtiyāṭ) and Dayah Authority - Asriadi; Irfan Fauzi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
This study examines the unique phenomenon of repeating Friday sermons (Khutbah) in Aceh, practiced as a precautionary measure (iḥtiyāṭ) to ensure ritual validity. While contemporary Islamic legal discourse tends to simplify worship practices, Acehnese society adopts a ritual thickening approach rooted in strict adherence to the Shafi'i school. This practice emerges as a response to theological anxiety regarding the potential invalidation of the muwalah (continuity) condition caused by operational pauses or technical interruptions during the sermon. This study aims to analyze the construction of Islamic law that legitimizes this practice and to uncover how religious authorities (Dayah) institutionalize it within the community. Employing a socio-legal approach within a qualitative framework, this study synthesizes the analysis of classical jurisprudential texts (turats) with phenomenological observations of congregants and preachers in Dayah-based regions. The findings confirm that sermon repetition is not an indication of incompetence or inefficiency, but rather a mitigative legal strategy grounded in the principles of Iḥtiyāṭ (precaution) and Sadd al-Dharīʿah (blocking the means to harm). Dayah scholars play a central role in constructing the narrative that this repetition serves as a theological safeguard to protect the validity of worship from doubt (syak). This study concludes that this phenomenon represents a Fiqh of Anxiety, where strict textual compliance functions as a psycho-religious mechanism to achieve inner peace.